Goal orientations, academic burnout and its relationship with academic engagement among public university students in Malaysia - Ahmad, Nor Aniza; Yoong, Lee Fong (Fakultas Ilmu Tarbiyah dan Keguruan, UIN Syarif Hidayatullah Jakarta, 2017)
This study is aimed to determine the relationship between goal orientations, academic burnout and academic engagement among undergraduate students in Malaysia. The respondents of this study consisted of 319 second year and third year undergraduate students who pursuing a Bachelor Degree of Education in three public universities in Malaysia. The research instruments used in this study included Motivated Strategies for Learning Questionnaire (MSLQ), Maslach Burnout Inventory-Student Survey (MBI-SS), and Utrecht Work Engagement Scale-Student (UWES-S). Furthermore, the results of this study revealed that academic engagement was significantly positively correlated with intrinsic goal orientation. Academic engagement was also found to be significantly positively correlated with extrinsic goal orientation. In addition, there was a significant negative correlation between academic burnout and academic engagement. The results of regression analysis denoted that intrinsic goal orientation, extrinsic goal orientation and academic burnout were significant predictors of undergraduate students’ academic engagement. The findings of this study emphasized the importance of goal orientations on academic engagement among undergraduate students. Intervention and prevention programs should be provided for the students, especially for those who are experiencing academic burnout.